2022
DOI: 10.3390/md20060383
|View full text |Cite
|
Sign up to set email alerts
|

Marine Chitooligosaccharide Alters Intestinal Flora Structure and Regulates Hepatic Inflammatory Response to Influence Nonalcoholic Fatty Liver Disease

Abstract: In this study, C57BL/6 mice were given an HFHSD diet for 8 weeks to induce hepatic steatosis and then given COSM solution orally for 12 weeks. The study found that the HFHSD diet resulted in steatosis and insulin resistance in mice. The formation of NAFLD induced by HFHSD diet was related to the imbalance of intestinal flora. However, after COSM intervention, the abundance of beneficial bacteria increased significantly, while the abundance of harmful bacteria decreased significantly. The HFHSD diet also induce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 47 publications
0
13
0
Order By: Relevance
“…CA (Mu et al, 2021) decreased LPS/TLR4, an LPS-mediated inflammatory pathway, and reduced TNF-α, IL-6 levels, thereby inhibiting dysregulation of lipid metabolism. LBPs (Gao et al, 2021) and COSM (Feng et al, 2022) inhibited indicators related to hepatic LPS/TLR4/NF-κB signaling pathway and attenuated the level of inflammation. HQT (Tang, 2019) and Compound Danshen Dripping Pills selectively targeted TLR4 and inhibited LPS-induced inflammatory mediator production by attenuating the LPS/TLR4/MyD88 pathway.…”
Section: Tcm Restores Intestinal Barrier and Alleviates Lps-induced I...mentioning
confidence: 94%
See 2 more Smart Citations
“…CA (Mu et al, 2021) decreased LPS/TLR4, an LPS-mediated inflammatory pathway, and reduced TNF-α, IL-6 levels, thereby inhibiting dysregulation of lipid metabolism. LBPs (Gao et al, 2021) and COSM (Feng et al, 2022) inhibited indicators related to hepatic LPS/TLR4/NF-κB signaling pathway and attenuated the level of inflammation. HQT (Tang, 2019) and Compound Danshen Dripping Pills selectively targeted TLR4 and inhibited LPS-induced inflammatory mediator production by attenuating the LPS/TLR4/MyD88 pathway.…”
Section: Tcm Restores Intestinal Barrier and Alleviates Lps-induced I...mentioning
confidence: 94%
“…The abundance of Desulfovibrio, a producer of LPS, was positively correlated with inflammation and LMD. Danlou Tablet (DLT) (Sun et al, 2020), DZSM (Guo et al, 2022), GQD (Liu, 2019), SLBZ (Zhang et al, 2018), DG (Li Y. et al, 2018), Chitooligosaccharide (COSM) (Feng et al, 2022), Rhizoma Coptidis (RC) alkaloids (He et al, 2016), Baicalin (Liu, 2016), Quercetin (Porras et al, 2017) and BBR (Xu, 2013) might ameliorate LMD by decreasing the abundance of Desulfovibrio to reduce LPS into the blood and inflammatory factors secretion. Notably, DLT (Sun et al, 2020), Gastrodin (Liu F. Y. et al, 2021) could downregulate the levels of inflammatory markers IL-1β, ICAM-1 and TNF-α, favoring the reversal of periaortic inflammation and reduction of plaque area in AS mice.…”
Section: Tcm Restores Intestinal Barrier and Alleviates Lps-induced I...mentioning
confidence: 99%
See 1 more Smart Citation
“…Feng et al revealed that COSM could dose‐dependently reduce IL‐6 levels and TNF‐α levels to attenuate inflammatory responses in NAFLD mice; serum LPS levels (representing the degree of intestinal barrier obstruction) were also significantly decreased in the COSM group. Additionally, COSM was able to improve intestinal barrier structure by increasing beneficial bacteria such as thick‐walled and proteobacteria in NAFLD mice as well as inhibit LPS/TLR4/NF‐κB signaling pathway (Feng et al, 2022).…”
Section: The Use Of Natural Products In the Treatment Of Nafldmentioning
confidence: 99%
“…Additionally, COSM was able to improve intestinal barrier structure by increasing beneficial bacteria such as thick-walled and proteobacteria in NAFLD mice as well as inhibit LPS/TLR4/NF-κB signaling pathway (Feng et al, 2022).…”
Section: Protective Effect Of Polysaccharide Components Against Nafldmentioning
confidence: 99%